The Gospel of Divine Mercy in King Lear - Grzegorzewska, Małgorzata (Text Matters: A Journal of Literature, Theory and Culture, 2021)
The paper discusses Shakespeare’s preoccupation with the Christian notions of divine love, forgiveness and justice in The Tragedy of King Lear. In my reading I employ Jean-Luc Marion’s phenomenological reflection on the givenness of love and Hans-Urs von Balthasar’s theology of Paschal mystery. I take issue with the Marxist and existentialist interpretations of Shakespeare’s tragedy which prevailed in the second half of the 20th century. My aim is not a simple recuperation of the “redemptionism” of the play, but an in-depth consideration of Christian allusions in the play which may tie love and forgiveness to justice and throw light on the ending of King Lear.